IgG4-Related Sclerosing Disease Causing Spinal Cord Compression: The First Reported Case in Literature. (18th June 2019) - Merza, Nooraldin; Taha, Ahmed; Lung, John; Benderman, Anthony W.; Wright, Stephen E.
Abstract : Immunoglobulin G4-related disease (IgG4-RD) is known for forming soft tissue mass lesions that may have compressive effects. It is an extremely rare disease that most frequently affects the pancreas causing autoimmune pancreatitis. It can also affect the gallbladder, salivary glands, and lacrimal glands causing respective organ-specific complications. In our report, we describe an IgG4-RD case that affected the spinal cord. A 60-year-old female presented with cervical spinal cord compression caused by IgG4-RD leading to several neurological deficits. Pathological examination of the excisional biopsy of the mass revealed dense lymphoplasmacytic cells infiltration and stromal fibrosis with IgG4 and plasma cells. The patient showed a dramatic response to the administration of systemic steroids with almost resolution of her neurological symptoms. This case highlights the first case in literature for IgG4-RD of the extradural tissue causing spinal compression. Hereby, we also demonstrate the dramatic response of IgG4-RD to the administration of systemic steroids as the patient had no recurrence after 5 years of close follow-up, the longest reported period of follow-up reported in the literature to date.